Identification and characterization of mouse otic sensory lineage genes - Hartman, Byron H.; Durruthy-Durruthy, Robert; Laske, Roman D.; Losorelli, Steven; Heller, Stefan (Frontiers in Cellular Neuroscience, 2015)
Vertebrate embryogenesis gives rise to all cell types of an organism through the development of many unique lineages derived from the three primordial germ layers. The otic sensory lineage arises from the otic vesicle, a structure formed through invagination of placodal non-neural ectoderm. This developmental lineage possesses unique differentiation potential, giving rise to otic sensory cell populations including hair cells, supporting cells, and ganglion neurons of the auditory and vestibular organs. Here we present a systematic approach to identify transcriptional features that distinguish the otic sensory lineage (from early otic progenitors to otic sensory populations) from other major lineages of vertebrate development. We used a microarray approach to analyze otic sensory lineage populations including microdissected otic vesicles (embryonic day 10.5) as well as isolated neonatal cochlear hair cells and supporting cells at postnatal day 3. Non-otic tissue samples including periotic tissues and whole embryos with otic regions removed were used as reference populations to evaluate otic specificity. Otic populations shared transcriptome-wide correlations in expression profiles that distinguish members of this lineage from non-otic populations. We further analyzed the microarray data using comparative and dimension reduction methods to identify individual genes that are specifically expressed in the otic sensory lineage. This analysis identified and ranked top otic sensory lineage-specific transcripts including Fbxo2, Col9a2, and Oc90, and additional novel otic lineage markers. To validate these results we performed expression analysis on select genes using immunohistochemistry and in situ hybridization. Fbxo2 showed the most striking pattern of specificity to the otic sensory lineage, including robust expression in the early otic vesicle and sustained expression in prosensory progenitors and auditory and vestibular hair cells and supporting cells.